RM TAWAKAL CUSTOMER SATISFACTION ANALYSIS USING CSI AND IPA METHODS - Alvin Aprillia; Yunita Primasanti; Erna Indriastiningsih (International Journal of Economics and Management Research, 2022)
Apart from clothing and shelter, food is a basic human need. No wonder the culinary industry is growing rapidly in various cities in Indonesia. One of them is in Klaten, Central Java. An example of a restaurant business (RM) in Klaten is RM Tawakal Haji Rofi`atun. RM Tawakal is located in Popongan Hamlet, RT03, RW03, Tegalgondo, Wonosari, Klaten. Maintaining customer satisfaction requires quality control to meet customer needs and satisfaction.The purpose of this study was to determine customer satisfaction with the service quality of RM Tawakal. Respondents of this survey are RM Tawakal clients and surveyed data collection / surveyed. Data processing is based on the Customer Statistics Index (CSI) and Importance Performance Analysis (IPA). According to the survey, the final result of the calculation of the Customer Statistics Index (CSI) is 80.01%, and consumers are satisfied with the services provided, but not optimally. When tested using the Severity Performance Analysis (IPA) method,quadrant A contains six attributes. That is, there are six attributes whose service has not been maximized, and restaurants need to improve service.